A produção do pensamento geográfico no Brasil nos livros enviados para Exposição Universal de Chicago, EUA - Raimundo Jucier Sousa de Assis (Confins)
This paper deals with the Brazilian production of geographic thinking focused on the books about São Paulo, Pará, Bahia, and Ceará territories wrote to the Chicago World’s Fair, in 1983. We understood these books and their writers as the starting point and framework to the investigation, supplying a pool of useful references helping us to tell the history of the Brazilian geographic thinking and revealing what were the novelties on the Brazilian territory to the XIX century international world, mainly to the US.